Beverage ethanol exposures among infants reported to United States poison control centers. (3rd July 2021) - Gaw, Christopher E.; Lim, Casey G.; Korenoski, Amanda S.; Osterhoudt, Kevin C.
Abstract: Background: Case studies and small series have demonstrated that beverage ethanol may pose a serious poisoning hazard to infants. Intoxicated infants may not present with the classic signs or symptoms of ethanol poisoning. The objective of this study was to describe the epidemiology of beverage ethanol exposures among infants reported to the United States poison control centers. Methods: Data from the National Poison Data System were retrospectively analyzed for infants <12 months of age who were exposed to beverage ethanol from 2009–2018. Results: Over the 10-year study period, 1, 818 infant exposures to beverage ethanol were reported. Most exposures were single substance (95.2%), and the most common route of exposure was ingestion ( n = 1, 738). Infants 9–11 months were the most commonly exposed age group subset (45.3%). The annual number and rate of alcoholic beverage exposure increased by 37.5% and 42.9%, respectively, from 2009 to 2018. Of the 563 infants evaluated at a healthcare facility, 38% of exposures were hospitalized. Infants 0–5 months of age had higher odds of being admitted to a non-critical (OR: 2.35, 95% CI: 1.41–3.92) or critical care unit (OR: 2.39; 95% CI: 1.50–3.79) compared to infants 6–11 months of age. Infants 0–5 months of age were more likely to (OR: 4.65; 95% CI: 3.18–6.79) experience a serious outcome compared to infants ages 6–11 months. Five fatalities in infants <6 months old were documented. An in-depth case review identified improper storage and subsequent formula preparation with beverage ethanol as a common exposure mechanism. Conclusions: Beverage ethanol exposures among infants are associated with hospitalization, serious clinical effects, and mortality. Infants may present with atypical signs and symptoms of intoxication, requiring a high index of suspicion. Opportunities exist to reduce exposures by addressing improper storage of beverage alcohols.